The Cushing OK Crude Oil Futures Price Pass - Through to New York Harbor Reformulated RBOB Regular Gasoline Futures Price - Nguyen, Chu V. (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
This study utilizes an Autoregressive Distributed Lag model to investigate the nature of crude oil futures price pass-through since 2006. The empirical results reveal a very high but incomplete short-run pass-through rate from the crude oil futures price to the gasoline futures price of 0.849298 with a corresponding negative long-run pass-through rate of -0.2440894. These empirical findings suggest that traders in the U.S. oil and gasoline futures markets overreact to fluctuations in the crude oil futures price as evidenced by subsequent corrections made over the sample period. The result of the bounds test for a long-term relationship between these two futures prices is inconclusive. The empirical findings further suggest that U.S. futures market traders considered futures prices of gasoline three weeks earlier in determining the current trading price while taking only one week to respond completely to the shock in the crude oil futures price. The empirical findings of this investigation may address the core elements of the price dynamics of the crude oil and gasoline futures markets and advance inquiry into assessment tools that could manage a very complex market challenge, especially for policy makers in countries with transitional economies in Eastern Europe, Caucasus and Central Asia.